HUBUNGAN PERILAKU PEMBELAJARAN DARING TERHADAP KEJADIAN MUSCOLOSKELETAL DISORDER (MSDS) SELAMA MASA PANDEMI COVID 19 PADA MAHASISWA S1 KEPERAWATAN UPN VETERAN JAKARTA TAHUN 2022 - Hilmi Yoda, (2022)
The very rapid spread of COVID-19 cases has an impact on all sectors, one of which is the education sector, where almost all schools and universities carry out online learning in order to anticipate the spread of covid 19. By implementing online learning, there are changes in student activities that cause several physical and health complaints. on students. Poor body position, performing many tasks for a long enough duration while doing online learning can result in muscle contractions in certain body parts which can trigger complaints of musculoskeletal disorders (MSDS). Knowing the correlation of online learning behavior to musculoskeletal disorders (MSDS) during the covid 19 pandemic period for undergraduate Nursing students at UPN Veterans Jakarta in 2022.This research method is a quantitative design using a cross sectional analytic research design. The population of this study were undergraduate students of Nursing at UPN Veteran Jakarta. In this study using accidental sampling technique. Based on the results of statistical analysis using the chi square test, a p value of 0.00 0.05 was obtained. This shows that H0 is rejected. There is a correlation of online learning behavior to musculoskeletal disorders (MSDS) during the covid 19 pandemic period for undergraduate Nursing students at UPN Veterans Jakarta in 2022.